Climate policy, interconnection and carbon leakage: The effect of unilateral UK policy on electricity and GHG emissions in Ireland - John Curtis; Valeria Di Cosmo; Paul Deane (The Economic and Social Research Institute (ESRI), 2013)
This paper examines the effect on Ireland's Single Electricity Market (SEM) of the UK's unilateral policy to implement a carbon price floor for electricity generation based on fossil-fuel. We simulate electricity markets and find that, subject to efficient use of the interconnectors between the two markets, a carbon price floor will lead to carbon leakage, with associated emissions in the Republic of Ireland increasing by 8% and SEM's electricity prices increasing by 2.4%. As the carbon price floor does not affect the number of ETS allowances no change is anticipated in aggregate European emissions. We also find that the EU's proposal to postpone ETS allowance auctions will reduce Irish emissions somewhat but that the trade opportunities associated with the UK carbon price floor means that emissions reductions in Ireland will be lower than might have been otherwise. A carbon price floor will result in substantial tax revenues and had the carbon price floor been implemented in Northern Ireland the larger share of taxes remitted would be paid by Republic of Ireland customers within the SEM. A carbon price floor in the Republic of Ireland is a potential policy option that would generate revenues in excess of exteuro250 million but associated electricity prices increases in excess of 17% would have significant negative welfare and competitiveness effects.
Keywords: 330